Handbook of the Sociology of the Military - Caforio, Giuseppe; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
Never before has there been so extensive a collection of what has been thought, said, and written about the sociology of the military. This accessible handbook is the first of its kind to delve into the sociological approach to the study of the military. This book is compiled of documents coming from various researchers at universities around the world as well as military officers devoted to the sector of study. Covered in this volume is a historical excursus of studies prior to contemporary research, interpretive models and theoretical approaches developed specifically for this topic, civic-military relations including issues surrounding democratic control of the armed forces, military culture, professional training, conditions and problems of minorities in the armed forces, an examination of the structural change within the military over the years including new duties and functions following the Cold War. This book is ideal for scholars of the subject as well as those coming to the sociology of the military for the first time.
General Introduction -- Some Historical Notes -- Social Research and the Military -- Theoretical and Methodological Orientations -- Models and Explanations for Military Organization: An Updated Reconsideration -- The Order of Violence -- The Military and the Use of Force -- Military Mobilization in Modern Western Societies -- Armed Forces and Society -- Civil-Military Relations -- Democratic Control of Armed Forces -- The Military as a Tribe among Tribes -- Soldiers and Governments in Postpraetorian Africa -- Military Families and the Armed Forces -- Implications for Military Families of Changes in the Armed Forces of the United States -- Inside The Military -- Military Culture -- Military Officer Education -- Women in the Military -- Diversity in the Armed Forces -- Unionization of the Military -- Trends in the Military: Conversion and Restructuring -- Restructuring of the Armed Forces -- Conversion of the Military -- The Decline of the European Mass Armies -- Technology, Organization, and Power -- New Missions -- Building Flexible Forces for the 21st Century -- A Soldier Is a Soldier Is a Soldier!? -- Conclusions -- Conclusion.
Keywords: Social sciences; Management; Political science; Sociology; Social Sciences; Sociology, general; Political Science; Management; Electronic books